The vocational counseling of youth concerning working trades: problems and prospects - Zakatnov, Dmytro (Professional Pedagogics, 2011)
The article analyses a state and reveals organizational-pedagogical conditions for solving a problem of vocational counseling of youth concerning working trades.
Keywords: working trades; vocational counseling; organizational-pedagogical conditions of vocational counseling concerning working trades